Side‐by‐Side Alterations in Glycocalyx Thickness and Perfused Microvascular Density During Acute Microcirculatory Alterations in Cardiac Surgery. (January 2016) - Koning, Nick J.; Vonk, Alexander B. A.; Vink, Hans; Boer, Christa
Abstract: Objectives: Endothelial glycocalyx injury causes microcirculatory perfusion disturbances in experimental studies, but the relevance in a clinical setting remains unknown. We investigated whether glycocalyx dimensions are reduced after onset of CPB and whether this is associated with alterations in microvascular perfusion. Methods: The current observational study included 36 patients undergoing cardiac surgery without or with CPB, using either nonpulsatile or pulsatile flow. Sublingual microcirculatory perfusion was assessed perioperatively and analyzed for perfused vessel density and PBR, an inverse parameter of endothelial glycocalyx dimensions. Results: Perfused vessel density decreased after onset of CPB in parallel with an increase in PBR in both pulsatile and nonpulsatile groups. In the nonpulsatile CPB group, these alterations were still persistent in the ICU (PVD: T1 19.8 ± 2.8 mm/mm 2 vs. T3 15.3 ± 2.6 mm/mm 2 ; p = 0.004. PBR: T1 2.40 ± 0.35 μ m vs. T3 2.60 ± 0.31 μ m; p = 0.020). In the off‐pump group, perfused vessel density remained unaltered. An inverse correlation between perfused vessel density and PBR was detected. Conclusions: This study shows that endothelial glycocalyx dimensions decrease after onset of CPB and are closely related to microvascular perfusion when assessed with a novel, noninvasive technique.